Attitude of university students towards the use of female condoms (Research, Society and Development, 2023)
This research sought to evaluate knowledge, perspectives and practices regarding the use of female condoms by university students in a public institution. It also sought to characterize the sociodemographic and economic variables of the studied population, identifying barriers and accessibility to the use of female condoms. This is a quantitative, descriptive and cross-sectional study that will be carried out in a public higher education institution with 133 students. Data were collected using a structured and adapted form. Microsoft Office Excel 2010 version 14.0 for Windows and CEP opinion number 93114218.3.0000.5660 were used to stratify the data. It was studied that the academics were largely in the age group of 18 to 28 years old, or 90.22% of the sample, single 75.2%, fourth year of course 53.4%, live with their family, in their own residence, do not work and have an income of one minimum wage. The study's findings show that there are accessibility and barriers, and curiosity leads students to buy condoms at health facilities. The biggest barrier was the difficulty of insertion.